EFEKTIFITAS AROMATHERAPY LAVENDER TERHADAP PENURUNAN NYERI PERSALINAN: KAJIAN LITERATUR - Widianti Kuswara, Sani; Lestari, Selvia (Yayasan Putra Sukamanah Sejahtera, 2024)
Fear of labour pain is the most common reason for women. Labour pain usually occurs naturally, but severe pain levels can cause physiological changes in every body function. Many methods have been used for pain management, both pharmacological and non-pharmacological. One of the non-pharmacological methods to reduce pain is aromatherapy. Aromatherapy is an ancient healing process using pure aromatic plant essences such as highly concentrated essential oils or substances distilled from plants to take advantage of their therapeutic properties. The purpose of this literature review is to identify labour pain management. The design of this study is a literature review. Search articles using the CINAHL database, Pubmed, and Science Direct by entering synonyms and keywords to be used in the search. Then obtained, as many as five articles which Fulfill criteria inclusion, and further observations were made for review. The evaluation shows that aromatherapy with lavender oil can reduce labour pain and is an effective way to reduce the duration of labour. Most of the women were satisfied with this intervention. It was also found that aromatherapy with lavender essence is a simple, inexpensive, non-invasive, and effective intervention to reduce labour pain and has no harmful side effects.